A Game Changer: Functional Nano/Micromaterials for Smart Rechargeable Batteries. (14th August 2019) - Ryu, Jaegeon; Song, Woo‐Jin; Lee, Sangyeop; Choi, Sungho; Park, Soojin
Abstract: The imperative to electrify the transport sector in the past few decades has put millions of electric vehicles on the road worldwide with an extended mile range from critical technological breakthroughs in developing the rechargeable energy storage systems, which also covers electronic devices and smart grid applications. However, the available energy density of prevailing systems in the market (i.e., batteries) is reaching its boundaries due to the limited choice of electrochemical reactions that necessarily depend on the thermodynamics and kinetics of the components (e.g., cathode, anode, electrolyte, separator, and current collectors). Reaching the high energy density of batteries exploits new redox chemistry such as sensitive metal anodes, insulating and highly dissolving sulfur cathodes, etc., thus requiring novel designs of various multiscale functional materials to address the corresponding issues. Here, the recent achievements on the designs of smart functional materials for emerging problems in the whole range of systems are discussed: i) interfacial control/kinetic regulation of Li–S battery; ii) self‐healing‐driven structural stability in the electrode and electrolyte; iii) ion‐sieving functional membranes for selective scavenging capability; and iv) functional materials to ensure battery safety. Abstract : Smart, functional materials in the nano/microscale that are specially designed for rechargeable batteries are comprehensively discussed. The designed materials aim to address the issues in interfacial chemistry of Li metal anodes and sulfur cathodes, integration of electrodes or electrolytes during unusual deformations, selectivity of membranes, and safety of systems.